EMIGRATIONS TO PROVINCE OF EDIRNE (1853-1897) - KALAYCI, İsa and ÇATAL, Ahmet Caner (Atlas Journal, 2018)
Turkey that connects with southwest Asia and the Europe lies at the intersection of migration routes. The city of Edirne was a former capital of the Ottoman Empire between1365 and 1453 was affected from migration flows throughout the history. In the second half of the 19th century, the Ottoman Empire began to lose territories and subjects those who believed shared culture and security under the Ottoman Empire migrated to inner provinces of the Empire. The Crimean War (1853-1856) and the Ottoman-Russian War (1877-1878, aka 93 War) were important events increasing migration in the province of Edirne. As a result of losing territory in these wars, people who were oppressed by Russians and Bulgarians in Crimea, the Caucasus and the Balkans migrated into the middle of the Ottoman Empire massively. In the 19th century, Edirne was exposed to migration like human flood. Not only temporary, but also permanent migration movement, Edirne seemed to be break water. It was the first stop for people who sought to go to Istanbul (Dersaadet) or Anatolia. The people of Edirne did their share to cover needs of migrants excessively. Migrants in Edirne were privileged from taxes temporarily. The allocation of space was the important aid for migrants. Even though the Ottoman politicians and people of Edirne made significant efforts, public order issues were seen deriving from the migration. This paper focuses on the province of Edirne within roughly 44 year period. It is aimed to put forward to demographic shifting historically. In terms of time period, it is hard to find a special research focusing on the history of Edirne, so it contributes to the importance of the paper. In this paper, documents in the ottoman archives of the prime ministry, memories and secondary sources have been benefited. It is put forward that population of migrants, the size of the territory given to the migrants, other aids to migrants and issues of public orders within the province of Edirne